Size and position of the reproductive tract impacts fertility outcomes and pregnancy losses in lactating dairy cows - Madureira, A. M. L.; Poole, R. K.; Burnett, T. A.; Guida, T. G. [UNESP]; Edwards, J. L.; Schrick, F. N.; Vasconcelos, J. L. M. [UNESP]; Cerri, R. L. A.; Pohler, K. G. (Elsevier B.V., 2020)
There are multiple factors that contribute to reduced fertility in lactating dairy cows. Recently, a reproductive tract size and position score (SPS) system was developed as a management tool to identify dairy cows with decreased fertility. The aim of this study was to evaluate the association between the SPS on fertility outcomes such as ovulation failure, pregnancy per artificial insemination (P/AI), concentration of pregnancy-associated glycoproteins (PAGs), and pregnancy loss in lactating dairy cows. Primiparous and multiparous lactating Holstein cows (n = 869) were enrolled at two locations. Location 1 (Loc. 1) in Minas Gerais, Brazil (n = 613) and location 2 (Loc. 2) in Agassiz, British Columbia, Canada (n = 256). At the time of AI (d 0), cows were classified as SPS (small [SPS1], medium [SPS2], or large [SPS3] sized reproductive tract) and ovulation failure was determined at 48 h and 7 d post-AI via ultrasonography (Loc. 2 only). Blood samples were collected on d 24 and 31 of gestation for quantification of PAGs and pregnancy diagnosis was performed via ultrasonography at d 31 and 60 post-AI (Loc. 1) and at d 31 +/- 3 and 60 +/- 3 post-AI (Loc. 2). Cows diagnosed pregnant at d 31 post-AI but not pregnant at d 60 were defined to have undergone late embryonic pregnancy loss. Parity was found to impact SPS (P < 0.01), as primiparous cows had a higher frequency of SPS1 and lower frequency of SPS3 when compared with multiparous cows (SPS1: 42.6 vs. 15.0%; SPS3: 7.0 vs. 22.0%, respectively). Cows classified as SPS3 had greater ovulation failure at 48 h (P = 0.04) and 7 d post-AI (P = 0.05). Cows classified as SPS1 had greater P/AI when compared to SPS2 and SPS3 (45.9 +/- 3.3 vs. 37.4 +/- 2.6 and 29.1 +/- 3.5%, respectively; P = 0.004). There was no interaction between parity and SPS on P/AI. Pregnancy loss between 31 and 60 d post-AI was increased in cows classified as SPS3 compared to SPS2 and SPS1 (24.3 +/- 0.05 vs. 11.6 +/- 0.02 and 9.4 +/- 0.02%, respectively; P = 0.04). Cows classified as SPS1 and SPS2 had greater concentrations of PAGs at 31 d post-AI when compared to SPS3 at both Loc.1 (P < 0.01) and Loc. 2 (P < 0.01). There was no interaction between SPS and pregnancy loss on PAGs at 24 and 31 d postAI for either Loc. 1 (P = 0.75 and P = 0.76, respectively) or Loc. 2 (P = 0.61 and P = 0.81, respectively). In conclusion, cows that were classified as SPS3 had greater ovulation failure, reduced P/AI, similar concentrations of PAG on d 24, but decreased on d 31, and a greater incidence of pregnancy loss. Thus, size and position of the reproductive tract is associated with fertility and this scoring system could be used to make reproductive management decisions on dairy operations. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Dairy cattle; Reproductive tract size and position score; Fertility; Pregnancy loss